PEMBERIAN PUPUK ORGANIK SUPER NATURAL NUTRITION (SNN) PADA TANAMAN SELADA (Lactuca sativa, L) DI TANAH ULTISOL - Surtinah Surtinah (Universitas Lancang Kuning, 2009)
ABSTRACTThe purpose of this research was done by using completely the randomized design of cunstruction which consist of six treatments with three replications, such as : control, SNN 0,5 cc / l; SNN cc / l ; SNN 1,5 cc / l ; SNN 2 cc / l ; and SNN 2,5 cc / l. The parameter that we search are from the heigt of the plant, the count of the leaf, the length of the leaf and the fresh weight of the plant it self. The data which analyses is used Polynomial regression. The results showed that, the concentrate of SNN that given the hights product of lettuce is 2.5 cc / l of water.